PENGGUNAAN ABU SEKAM PADI SEBAGAI ADSORBEN DALAM PENGOLAHAN AIR LIMBAH YANG MENGANDUNG LOGAM Cu - Mochtar Hadiwidodo (Diponegoro University, 2008)
The industrial development have been increased together with the increasement of the society need. Theindustrial development will produce another product in the shape of dump that will be throw away to theenvironment. One of the industrial dump was the industrial dump from the copper industry that containshard metal copper (Cu). One of the way to manufacture dump is with the adsorption process of the riceplant dust husk. This research has the aim to know the adsorption ability of the rice plant dust husk indecreasing the concentration of Cu metal in the artificial water dump and it was done with batch processand continuous. The batch experiment use 10, 20, 30 gram adsorben for each media size variation 10-30mesh and 30-50 mesh. Has the highest decreasing efficiency in the weight of 30 gram (30-50 mesh) that is52,81%-87,80%. In the continuous experiment, it was done in the column with 2 inch diameter and with222 ml/menit debit. The result was the highest decreasing efficiency until 94,98%-97,10%. Speed constanvalues (k1) 0,00743-0,0160 ml/mg.second with adsorp capacity(q0) 0,7734-1,3376 mg/g.